In vitro induction of neutrophil extracellular traps by SARS-CoV-2 is biased by extracellular mitochondria - Jakub Janko; Monika Sláviková; Boris Klempa; Peter Celec; Peter Celec; Michal Pastorek (Acta Virologica, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has a highly variable course that is dependent on the host immune system reaction. Lung tissue damage, endothelial dysfunction, and microthrombosis in severe COVID-19 is linked to neutrophilia and the production of neutrophil extracellular traps (NETs). Previous studies have shown that NETs are involved in the pathology of COVID-19 and that the virus itself induces NET formation, although the underlying mechanisms are not clear. In this study, we aimed to investigate the induction of NETs by SARS-CoV-2 in vitro. We have found that both, infectious and heat-inactivated virus induce NETs formation. Surprisingly, cell culture media derived from uninfected Vero cells exhibit similar potency. This suggests that NET inducers other than the virus might be involved. Mitochondria released from dying cells during SARS-CoV-2 infection acting as damage-associated molecular patterns (DAMPs) were identified as potential contributors to neutrophil activation and NET formation. Our findings point to an important source of bias when analyzing NETs induction by SARS-CoV-2 in vitro, but also the immune reaction to viruses in general. Further implications for the understanding of COVID-19 pathogenesis remain to be elucidated.